Science, Democracy and Relativism : the Production and Dissemination of Scientific Knowledge from the Viewpoint of Communitarian Epistemology. - Shekeris, Haris (Cambridge Scholars Publishing, 2014)
Science, Democracy and Relativism proposes and defends the thesis that scientific knowledge is produced through a process of argumentation and consensus among relevant communities of scientists, and that it is disseminated to other epistemic communities according to communitarian epistemology. Such a thesis considers scientific knowledge as unashamedly relative; however, this is regarded as a good thing for democracy, as it views knowledge as a matter of deliberation rather than something to ...